Blockchain in maritime: applications, effects and challenges - Zhao Li; Zhao Li; Yongqiang Sun (Frontiers in Marine Science)
The shipping market involves multiple stakeholders, including cargo owners, shipping companies, and maritime authorities. To prevent issues such as information concealment and privacy breaches, these stakeholders often establish complex and multi-layered data exchange processes, which significantly reduce the operational efficiency of the shipping market. Decentralized blockchain technology can prevent data tampering, thereby establishing an effective consensus mechanism among multiple parties. This paper first summarizes the application scenarios of blockchain technology in the shipping market, including supply chain management, smart contracts, port management, crew management, marine insurance, and environmental protection. Subsequently, using real-world cases such as TradeLens, CargoX, COSCO SHIPPING Hi ECO, and Insurwave, the advantages of blockchain technology in enhancing shipping efficiency and reducing costs are elaborated. Finally, the challenges of applying blockchain technology in the shipping market, from both technical and regulatory perspectives, are outlined.